2018
DOI: 10.1002/cmdc.201800327
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships of Antiplasmodial Pantothenamide Analogues Reveal a New Way by Which Triazoles Mimic Amide Bonds

Abstract: Pantothenamides are potent growth inhibitors of the malaria parasite Plasmodium falciparum. Their clinical use is, however, hindered due to the ubiquitous presence of pantetheinases in human serum, which rapidly degrade pantothenamides into pantothenate and the corresponding amine. We previously reported that replacement of the labile amide bond with a triazole ring not only imparts stability toward pantetheinases, but also improves activity against P. falciparum. A small library of new triazole derivatives wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 35 publications
4
17
1
Order By: Relevance
“…An important point to consider in drug synthesis and design is that triazoles can mimic amide bonds in different ways ( Figure 27 ). In some cases, the lone pair of triazole N-2 mimics the carbonyl oxygen of the amide bond, instead of N-3, which is similar to the case of triazole derivatives of pantothenamides, where the arrangement of triazole is consistent with the similar IC 50 values of compounds containing the amide bond and their triazole analogues [ 119 , 120 ].…”
Section: 123-triazoles In Other Mimeticsmentioning
confidence: 82%
“…An important point to consider in drug synthesis and design is that triazoles can mimic amide bonds in different ways ( Figure 27 ). In some cases, the lone pair of triazole N-2 mimics the carbonyl oxygen of the amide bond, instead of N-3, which is similar to the case of triazole derivatives of pantothenamides, where the arrangement of triazole is consistent with the similar IC 50 values of compounds containing the amide bond and their triazole analogues [ 119 , 120 ].…”
Section: 123-triazoles In Other Mimeticsmentioning
confidence: 82%
“…Our data indicate that T. gondii parasites are unable to scavenge sufficient downstream intermediates in the CoA biosynthesis pathway from their host cells, including CoA, for their survival, and therefore must maintain their own active CoA biosynthesis pathway. The requirement for CoA biosynthesis in T. gondii , coupled with the intense investigation of this pathway as a drug target in P. falciparum 27, 37, 4861 , suggests that further characterisation of Tg PanK, and the CoA biosynthesis pathway in T. gondii , could yield novel drug targets for chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 1 is however rapidly hydrolyzed by pantetheinases (vanins) in fresh blood, precluding in vivo investigations. Interestingly, several studies have shown that such pantothenamide derivatives can be rendered more stable, while maintaining their biological activity, by chemical modifications at the labile amide, [31][32][33][34][35] the geminal dimethyl, [36][37] or the β-alanine moiety, [38][39] warranting further investigations.…”
Section: Discussionmentioning
confidence: 99%